Emotional intelligence can make a difference: The impact of principals' emotional intelligence on teaching strategy mediated by instructional leadership. (January 2020) - Chen, Junjun; Guo, Wei
This paper reports on a study that examined the effect of school principals' emotional intelligence, and their instructional leadership, on improving teachers' instructional strategies. A sample of 534 primary teachers from 54 primary schools in China was approached and invited to respond to a questionnaire. Structural equation modelling identified the relationships between three constructs – Wong's Emotional Intelligence Scale, the Principal Instructional Management Rating Scale, and the Instructional Strategy Scale – and between the dimensional levels. The study confirmed the theoretical proposition that principals' EI and their instructional leadership behavior are influential factors with regard to teachers' instructional strategies. The findings are of particular interest because they include the element of emotional intelligence for improvement of teaching practice and evaluating the effectiveness of the principal.